IM-sgi an interface model for shape grammar implementations - Andrade, Joana Maria Oliveira Tching de Abreu (2020)
This research arises from the interest in computing as offering new paradigms in the design practice. Information technologies are the driving force for progress in the processes of design, enabling new forms of creativity. The increasing sophistication of computer applications, their easier access, and lower cost have had a significant impact on design practices and can be regarded as a paradigm shift. The invention and creativity are thus seen as knowledge processing activities and can, at least partially, be carried out with the support of computer applications. In this context Shape Grammars (SG) as production systems of designs through rules have the potential to create designs with variable user input and the ability to evaluate a large number of alternatives that may lead to innovative designs. Most architects and designers use computers on their daily practice as a representation tool for their projects, but not as a facilitator or increaser of the creative process. SG computational implementations have the potential to enhance creativity with the test of a wide range of design options, helping the appearance of new solutions, either through the emergence of new shapes or by stimulating the designer’s creativity with the possibilities presented. As Architects and Designers haven't adopted existing SG computational implementations, that take advantage of computation to facilitate and enhance their work, could the problem be on the communication between the applications and the user? If the interface of the SG implementation does not allow the user to understand how to use it or how to control and make use of its results, it can’t be successfully used. With interest in SG implementations as creative partners in the creative process, our research starts with the analysis of existing SG implementations, trying to understand if they had the potential to be adopted by architects and designers in their practice and, if not, what could be done to lead to that objective. User Interface Inspection Methods were used to perform this analysis and allowed us to understand that there are interactions and communication issues that need to be addressed for SG implementations to be adopted by designers. Taking this direction, we understood that models of interaction between the user and SG implementations have already been developed. The present research proposal started from the analysis of the interaction model of Scott Chase, where he defines the different levels of interaction between the user and SG implementation, with more or less input from the user, establishing different ways to combine synergies to obtain new creative solutions. Taking this interaction model as a starting point, next, we must assure the correct communication between user and implementation occurs. The means of communication between these two agents is the computational interface. Understanding the importance of the interface to allow the user to know how to use the computational implementation and be able to produce results, our research presents the development of an interface model for SG implementations to help to take a step towards the adoption of SG for creative projects. For this, we used methods from Human-Computer Interaction discipline, and we also took Bastien & Scapin's "List of Ergonomic Criteria Guidelines" as guiding lines to define the Criteria of our interface model, called IM-sgi, Interface Model for Shape Grammar Implementations. Thus, IM-sgi, an interface model for SG Implementations, has the purpose of helping SG implementations developers to address the interface on the right path to a correct communication with the particular type of user that architects and designers are. Interface prototypes following IM-sgi criteria are finally developed and presented to test the suitability of the IM-sgi Model to SG implementations and validate the objectives we propose.